2018
DOI: 10.1097/pai.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Epidermal Growth Factor Receptor Gene Mutations Identified Using Pleural Effusion and Primary Tumor Tissue Samples in Non–Small Cell Lung Cancer

Abstract: We observed a high concordance rate between EGFR mutations identified using primary tumor tissue and corresponding pleural effusion samples by Amplification Refractory Mutation System. Thus, it is likely that pleural effusion sampling from advanced non-small cell lung cancer patients, especially those with adenocarcinoma, may be effective in EGFR-mutation screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
4
21
0
Order By: Relevance
“…In the 41 incidences where receptor status or genetic analysis was requested, the pleural fluid specimen was sufficient in 95% (39 out of 41) of cases. Other studies with a focus on this issue have found that pleural fluid samples can reliably provide genetic information that correlates with the primary malignancy [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In the 41 incidences where receptor status or genetic analysis was requested, the pleural fluid specimen was sufficient in 95% (39 out of 41) of cases. Other studies with a focus on this issue have found that pleural fluid samples can reliably provide genetic information that correlates with the primary malignancy [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In the 41 incidences where receptor status or genetic analysis was requested, the pleural fluid specimen was sufficient in 95% of cases (39/41). Other studies with a focus on this issue have found that pleural fluid samples can reliably provide genetic information that correlates with the primary malignancy [31][32][33][34].…”
Section: Characteristics Of Cytology Diagnostic Versus Non-diagnosticmentioning
confidence: 99%
“… 62 Moreover, the concordance between the primary tumor and pleural metastases concerning mutational alterations is very high. 63 Therefore, PF samples (CBs, smears, cytospins or liquid-based cytology) are considered suitable alternatives to tissue biopsy for molecular studies, provided they are not paucicellular. 64 , 65 The adequacy of specimens for molecular testing should be determined by assessing cancer-cell content and deoxyribonucleic acid (DNA) quantity and quality.…”
Section: Biomarkers Of Malignant Effusionsmentioning
confidence: 99%